PERANAN KEBIJAKAN AKUNTANSI PEMERINTAH DAERAH DALAM MENINGKATKAN KUALITAS LAPORAN KEUANGAN - Ratna Ratna; John Sihar Manurung, Darmawati, Tosanov T.P. Napitupulu, Budi Indra Syahdewa (CV. Adiba Aisha Amira, 2023)
This study aims to analyze local government accounting policies in Indonesia to determine whether or not the performance of financial managers partially affects the quality of financial statements. In realizing this, the government needs to improve the performance of financial managers for better quality financial reports. The research method used is a literature study with a qualitative approach. Data sources are obtained through a search for articles related to accounting policies carried out by local governments in preparing financial statements. Data analysis techniques are carried out by triangulating from various literature sources. The results of the study state that local governments need to prepare financial statements in accordance with Law Number 17 of 2003 which refers to Government Accounting Standards (SAP). As a derivative of the regulation, the government has issued Government Regulation Number 24 of 2005 which is updated with Government Regulation Number 71 of 2010 concerning SAP. With these regulations, the basis for recording government accounting changes from the cash basis to the cash basis to accrual and to the full accrual basis.